THE IMPORTANCE OF BIOLOGICALLY ACTIVE ORGANIC COMPOUNDS IN AGRICULTURE - Nematova M.Sh. (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
Abstract: In recent years, meeting the demand of the national economy for biologically active compounds (BACs), discovering new compounds, developing their production technologies, and implementing them in practice have become one of the most urgent tasks of modern chemistry. Among physiologically active substances, phenoxyalkyl acids and their derivatives exhibit the highest biological activity, which explains their wide range of applications. These compounds are widely used as selective herbicides affecting dicotyledonous plants and are applied on millions of hectares of agricultural land, including cereal crops and pastures.